Analisis Pengolahan Emas Menggunakan Sistem Hidraulik Mekanik di Daerah Rarowatu Kabupaten Bombana Provinsi Sulawesi Tenggara - Bakri, Hasbi; Anshariah; Asri, Al (Jurnal of Mining Insight, 2023)
Each processing using hydraulic system produces waste, tailing, containing gold. This research aimed to find out the cause of the losing and to find out the appropriate hydraulic system. It was conducted by taking data on the slope of the sluice box, the speed of materials flow, processed materials, and production results per day. The obtained data were then analyzed throughout comparing the values in the five research sites. The result indicated that in pit one the slope of sluice box was 150 with the flow speed was 2.05m/s resulted in 0.180 kg gold from 26.3 m3. In pit 2, the slope and the speed were 15o and 2.05 m/s respectively which this resulted in 0.180 kg gold of 26.3 m3. In pit 3, the slope and the speed were 12o and 1.92 m/s which resulted in 0.159 kg gold of 31.2 m3. In pit 4, the slope and the speed were 13o and 1.99 m/s which resulted in 0.148 kg gold of 28.3 m3. In the last pit, the slope and the speed were 15o and 2.01 m/s which resulted in 0.197 kg gold of 32.4 m3. The comparison indicated that the series of the hydraulic system which had ideal working efficiency was the one which had 2 m/s speed flow with the slope of sluice box was 15o. The slope was much better than 13o and 12o. The influencing factors for the loss were the speed of the flow and the slope of the sluice box